2016
DOI: 10.1155/2016/7287563
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Preferences of the Grey Parrot in Heterogeneous Vegetation Landscapes and Their Conservation Implications

Abstract: The wild Grey Parrot Psittacus erithacus Linnaeus suffers from many habitat use challenges in the wake of extensive deforestation in its endemic range of West and Central African rainforests. To determine effects of these challenges on the bird species, seasonal densities of the Grey Parrot were determined using line transects in major heterogeneous vegetation types in the Korup Rainforest, south-western Cameroon. Results of the study highlight habitat preferences of this species on a seasonal base and under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…The study was conducted in and around Korup National Park (KNP) in Southwest Cameroon ( Figure 1) congruent with the study area of the surveys in 2008-2010 by Tamungang et al (2016). Surveys were done between 23 March and 4 June 2016 during the pre-breeding season (pers.…”
Section: Study Areamentioning
confidence: 95%
See 3 more Smart Citations
“…The study was conducted in and around Korup National Park (KNP) in Southwest Cameroon ( Figure 1) congruent with the study area of the surveys in 2008-2010 by Tamungang et al (2016). Surveys were done between 23 March and 4 June 2016 during the pre-breeding season (pers.…”
Section: Study Areamentioning
confidence: 95%
“…The rainforests of the Korup region in Southwest Cameroon are still largely unfragmented (Kupsch et al 2019) and should therefore be an important stronghold of the species. Based on survey data from 2008 to 2010, Tamungang et al (2013) provided a population estimate for Southwest Cameroon as well as a more detailed assessment on habitat preferences in three landscape types (Tamungang et al 2016), however, Martin et al (2014b) criticised both their field and analysis methodology as deficient and prone to biases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other importance of a secondary forest to a primary forest for the Grey Parrot are that trees may be less congested and therefore provide good visibility for security thereby reducing predator access to nest contents. In a similar study carried out by Tamungang et al (2016a) in the South West Region of Cameroon, it was observed that the population of the Grey Parrot was higher in mixed secondary and farmland outside the Korup National Park than inside the park area (which was mainly primary forest).…”
Section: Nests Density and Tree Species Used By The Grey Parrotmentioning
confidence: 77%